Thanks for the Memories: On the Translation of Phil 1.3 - Holloway, Paul A. 1955- (2006)
According to the natural sense of the Greek, Phil 1.3 should be translated something like, ‘I give thanks to my God for every remembrance of you’. Scholars have rejected this interpretation without explanation, presumably because the thought of Paul thanking God for pleasant memories seems too odd even to be considered. Philippians, however, is a letter of consolation, and pleasant memories were a common source of consolation in Hellenistic–Roman antiquity. Read in the context of ancient consolation, from which there compelling parallels, the natural sense of 1.3 makes excellent sense. Accepting this interpretation solves other outstanding exegetical problems in Phil 1.3–11.